Kinetic Models for Glucosamine Production by Acid Hydrolysis of Chitin in Five Mushrooms - Pin Zhang; Manote Sutheerawattananonda (International Journal of Chemical Engineering)
In this paper, glucosamine was produced by acid hydrolysis of five mushrooms. The glucosamine yields were investigated, and the optimum conditions were obtained as follows: acid type, sulfuric acid; acid concentration, 6 M; ratio of raw material to acid volume, 1 : 10; hydrolysis temperature, 100°C; and time, 6 h. Under these conditions, the glucosamine conversion from chitin content reached up to 92%. The results of hydrolysis kinetics indicated that hydrolysis of five mushrooms to glucosamine followed zero-order kinetics. Moreover, the relatively low activation energy for hydrolysis of straw mushroom (18.31 kJ/mol) and the highest glucosamine yield (56.8132 ± 3.5748 mg/g DM, 0.9824 g/g chitin) indicated that hydrolysis of straw mushroom was energy-saving. Thus, sulfuric acid hydrolysis of straw mushroom for glucosamine production should be considered as an efficient process for the future industrial application. However, further study is needed for glucosamine purification.